O papel do Ministério Público do Amazonas na concretização do mínimo existencial e na efetivação dos direitos fundamentais, em especial na saúde e na educação - Jussara Maria Pordeus e Silva (2023)
The thesis investigates the contribution of the Brazilian Public Prosecutor's Office to the realization of the democratic regime, the effectiveness of fundamental and social rights, and the implementation of public policies in Brazil. The aim is to analyze whether the Public Prosecutor's Office, especially that of Amazonas, has an activist stance in favor of the realization of the existential minimum and its role in guaranteeing the protection of citizens' rights. The work is based on research into the constitutional evolution of the Public Prosecutor's Office and its profile as an inducer/propeller of fundamental and priority public policies. On the origins of judicial activism, the doctrine of Kmiec, Blackstone, Benthan and Schlesinger was sought. As for the scope of the conceptions of activism, we used the teachings of Barroso and Canotilho. The study of the dimensions of activism was based on Canon and, about the indicators of activism, on Marshall, Young, and Kmiec. When dealing with the currents of activism, we used the works of authors in favor of the normative current, such as Dworkin and Cappelletti, the favorable perspectives with reservations by Habermas and Garapon, and the opposing view by Ely. As for the developments of this current, we can mention the two axes (substantialist and proceduralist) mentioned by Werneck Vianna. Tate and Vallinder studied the analytical current. This is the result of an exploratory and descriptive study with a qualitative approach, using bibliographical research and a case study, with content analysis of the collected data. The first result of the thesis was the identification of doctrinal and jurisprudential methods for measuring the extent or degree of activism. The second was the development of an assessment tool capable of gauging the degree of activism of each Public Prosecutor's Office in the country. It can be applied by region and even by matter, as we used it for actions in the areas of education and health in the Public Prosecutor's Office of the State of Amazonas. Budgetary and financial data that cannot be obtained can be disregarded, as there are methods that do not use this indicator. The methods can be used separately if the researcher prefers, as it is possible to measure the results of each one. However, as they complement each other, for a result that is closer to reality, it is recommended to use those methods in which it is possible to obtain the most responses. The sample application carried out found that the activism of the Public Prosecutor's Office in the state of Amazonas is present but varies according to the matter and the circumstances.